2012
DOI: 10.1155/2012/143813
|View full text |Cite
|
Sign up to set email alerts
|

Voice-Related Quality of Life in Patients with Multiple Sclerosis

Abstract: Objective. To investigate the voice-related quality of life in a group of patients with multiple sclerosis. Participants. A total of 87 subjects (59 MS subjects and 28 controls) participated in this study. Main Outcome Measures. Variables included presence or absence of phonatory symptoms, duration of the disease, the expanded disability status scale (EDSS), the severity of fatigue, and depression. All patients were asked to fill the Voice Handicap Index. Results. The average age was 35.47 years + 10.92 with 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(6 citation statements)
references
References 25 publications
2
4
0
Order By: Relevance
“…Comparing the results obtained in this study with other studies, it can be noticed that in all studies the mean values of VHI are relatively low, indicating only a slight degree of self-reported voice disorder. The results are for instance: 15.64 and 16.68 in studies conducted by Bauer et al (n=36 and n=38 respectively), (Bauer et al, 2013, Bauer et al, 2015 and 5.92 in a study by Hamdan et al (n=59) (Hamdan et al, 2012). The higher value obtained in our study, indicating worse voice quality reported by the patients may result from the fact that the study was conducted on a much bigger group of patients (n=107) with a formal neurological MS diagnosis.…”
Section: Discussionsupporting
confidence: 40%
“…Comparing the results obtained in this study with other studies, it can be noticed that in all studies the mean values of VHI are relatively low, indicating only a slight degree of self-reported voice disorder. The results are for instance: 15.64 and 16.68 in studies conducted by Bauer et al (n=36 and n=38 respectively), (Bauer et al, 2013, Bauer et al, 2015 and 5.92 in a study by Hamdan et al (n=59) (Hamdan et al, 2012). The higher value obtained in our study, indicating worse voice quality reported by the patients may result from the fact that the study was conducted on a much bigger group of patients (n=107) with a formal neurological MS diagnosis.…”
Section: Discussionsupporting
confidence: 40%
“…A study of 59 participants with MS found no significant differences in the overall VHI score and subscores compared with the scores of healthy participants (VHI = 5.9, pVHI = 2.4, fVHI = 2.2, and eVHI = 1.4). 9 Only 8.7% of participants had serious vocal difficulties (VHI > 15). Contrary to that, the work by Natour et al analyzed VHI with 39 patients with MS, and a significant difference between patients with MS and healthy participants was noticed for both male and female participants (male VHI = 27.7 compared with VHI = 10.1 in the control group and female VHI = 19 compared with VHI = 11.4 in the control group).…”
Section: Discussionmentioning
confidence: 97%
“…The same conclusion was given in the study where only 12% of patients with MS described the difficulties of dysphonia. 9 On the other hand, the study of patients with MS performed by Natour showed significant differences in the self-assessment of vocal difficulties. 10 VHI was used, and a significant difference was observed between the total score and all subscores that were higher for patients with MS than the control group.…”
Section: Introductionmentioning
confidence: 99%
“…According to the literature, 5,[11][12][13][14] we included the following factors as potential variables associated with improvement of voice intensity (TABLE 1).…”
Section: Methodsmentioning
confidence: 99%
“…M ultiple sclerosis (MS) is a progressive, degenerative neurologic disease leading to demyelination and neurodegeneration involving different parts of the motor system, 1 including control systems for speech and voice. 2,3 Vocal disorders are common problems in people with MS. 2 The predominant voice impairments are harshness, breathiness, phonatory instability, 3 inability to maintain adequate adduction for phonation, 4 vocal fatigue, 5 and higher variability in fundamental frequency and sound pressure level (SPL). Consequently, the voice during conversation is unstable and hypophonic, leading to difficulties at work, participating in conversations with a wide range of people, using the telephone, and communicating in noisy environments.…”
mentioning
confidence: 99%